An Analysis of Illocutionary Acts in Taylor Swift’s Speech at NYU's 2022 Commencement - Sanerita T. Olii; Devita A. Humiang; Ignatius J. C. Tuerah (Journal of English Culture, Language, Literature and Education, 2023)
This present study offers a comprehensive analysis of the illocutionary acts in Taylor Swift's commencement speech delivered at New York University (NYU) in 2022. Illocutionary acts, a crucial component of speech acts theory, encompass the speaker's intended communicative functions, such as asserting, commanding, questioning, or expressing emotions. Taylor Swift's speech is examined in the context of illocutionary acts to uncover the underlying intentions and rhetorical strategies used in the address. Illocutionary acts refer to speech acts aimed at achieving specific communicative functions or goals. Pragmatics plays a helpful role in comprehending how speakers employ language to accomplish their communication objectives and how listeners interpret these utterances within the given context. It involves considering how speakers organize their intentions based on the individuals they are communicating with, the location, timing, and circumstances. This study analyzes the illocutionary acts performed by Taylor Swift in her Commencement speech at New York University (NYU). This study aims to identify and describe the meaning of the utterances used by Swift in her speech using qualitative methods. The results indicate that Swift utilized 94 utterances of illocutionary acts in her speech, including representative 33 utterances, expressive 32 utterances, declarative 13 utterances, directive 9 utterances, and commissive 7 utterances. Analyzing speech acts helped advance our understanding of the speaker's intentions and communicative goals. Without this understanding, communication can be hindered by misinterpretations and misunderstandings.